Evaluación del método electrostático en el beneficio y concentración de minerales. - Patiño Loján, Jorge Xavier (2004)
The work approaches the phenomenon related with the application of the electrostatic method for the benefit of minerals electric drivers that could be used for the exploitation of the same ones, in the mines of the Republic of the Ecuador, keeping in mind the inefficacy and the negative environmental effect of the traditional methods as the amalgamation and cianuration being highly toxic in the locations with reduced reservations of minerals with these characteristics, like it is the case of the gold. The parameters of operation of the equipment and the design variants that assure the efficient operation of the same one settle down. It is described the technology of production of the different parts and components for a perfected design variant, in the team installed in the ISMM of Moa - Cuba. He/she is carried out the installation process and assembly of their different elements, besides the setting tests in march and control of quality using for it minerals as the ilmenitr and chromite. Starting from the chosen experimental plan and after the process of preparation of the samples, results are obtained that they endorse the feasibility of evaluation of the method and their capacity for an efficient separation of minerals electric drivers.